Hybrid Decentralised Energy for Remote Communities: Case Studies and the Analysis of the Potential Integration of Rain Energy - Ying Miao; Yu Jia (Journal of Sustainable Development of Energy, Water and Environment Systems, 2014)

(untitled)
For remote underdeveloped and sparsely populated regions, the use of national power grids to provide electricity can be both unsustainable and impractical. In recent years, decentralised renewable power has gained popularity, endowing social benefits to the local inhabitants through clean rural electrification. However, power reliability and system autonomy are often the primary technical concerns as current systems are largely single source reliant. Hybrid power systems that utilise multiple complementary renewables can help to reduce the dependency on conventional unclean options. A few selected case studies for both single source and hybrid power systems are reviewed, analysing critical success factors and evaluating existing difficulties. The additional integration of the novel rain-powered kinetic-to-electric generator technology to the existing hybrid model is analysed. As with development in general, there is no one-size-fits-all solution to bringing power to remote communities and the most sustainable solution should be found through analysing local resources, environmental conditions and maximising local involvement.